2008
DOI: 10.1016/j.cnsns.2006.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of particle trapping in the wave-particle interaction

Abstract: The saturated dynamics of a Single Pass Free Electron Laser is considered within a simplified mean field approach. A method is proposed to increase the size of the macro-particle, which is responsible for the oscillations of the intensity of the wave. This approach is based on the reconstruction of invariant tori of the dynamics of test particles. To this aim a dedicated control term is derived, the latter acting as a small apt perturbation of the system dynamics. Implications of these findings are discussed i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Working along these lines, it was shown that QSS can be successfully interpreted as equilibria of the collisionless Vlasov equation which appears to rule the dynamics of a broad family of long range models, when recovering the continuum picture from the governing discrete formulation. The average characteristics of the QSS, including the emergence of out-of-equilibrium transitions, can be analytically predicted via a maximum entropy variational principle, pioneered by Lynden-Bell in [14] and more recently revisited with reference to paradigmatic long-range applications [7,8,15]. As we shall clarify in the forthcoming sections, the predictive adequacy of the Lynden-Bell violent relaxation theory has been so far solely assessed for a very specific class of initial conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Working along these lines, it was shown that QSS can be successfully interpreted as equilibria of the collisionless Vlasov equation which appears to rule the dynamics of a broad family of long range models, when recovering the continuum picture from the governing discrete formulation. The average characteristics of the QSS, including the emergence of out-of-equilibrium transitions, can be analytically predicted via a maximum entropy variational principle, pioneered by Lynden-Bell in [14] and more recently revisited with reference to paradigmatic long-range applications [7,8,15]. As we shall clarify in the forthcoming sections, the predictive adequacy of the Lynden-Bell violent relaxation theory has been so far solely assessed for a very specific class of initial conditions.…”
Section: Introductionmentioning
confidence: 99%